2017
DOI: 10.3847/1538-4357/835/2/182
|View full text |Cite
|
Sign up to set email alerts
|

Multiband Observations of the Quasar PKS 2326–502 during Active and Quiescent Gamma-Ray States in 2010–2012

Abstract: Quasi-simultaneous observations of the Flat Spectrum Radio Quasar PKS 2326−502 were carried out in the γ-ray, X-ray, UV, optical, near-infrared, and radio bands. Using these observations, we are able to characterize the spectral energy distribution (SED) of the source during two flaring and one quiescent γ-ray states. These data were used to constrain one-zone leptonic models of the SEDs of each flare and investigate the physical conditions giving rise to them. While modeling one flare required only changes in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Such a large value is consistent with the apparent speed of jet components seen with radio Very Long Baseline Interferometry (VLBI), which can be as high as β app = 78 (Jorstad et al 2017). In previous modeling efforts, it was found that varying only the electron distribution was necessary to reproduce several states from FSRQs (e.g., D'Ammando et al 2013;Ackermann et al 2014;Buson et al 2014) although this is not always the case (e.g., Dutka et al 2013Dutka et al , 2017. For the SEDs of PKS 0346−27, we attempted to model all states varying only the electron distribution.…”
Section: Sed Modelingsupporting
confidence: 62%
See 2 more Smart Citations
“…Such a large value is consistent with the apparent speed of jet components seen with radio Very Long Baseline Interferometry (VLBI), which can be as high as β app = 78 (Jorstad et al 2017). In previous modeling efforts, it was found that varying only the electron distribution was necessary to reproduce several states from FSRQs (e.g., D'Ammando et al 2013;Ackermann et al 2014;Buson et al 2014) although this is not always the case (e.g., Dutka et al 2013Dutka et al , 2017. For the SEDs of PKS 0346−27, we attempted to model all states varying only the electron distribution.…”
Section: Sed Modelingsupporting
confidence: 62%
“…We then varied the size of the emitting region and the magnetic field to model the states. Therefore, based on the classification of Dutka et al (2013Dutka et al ( , 2017, all of the modeled flares from PKS 0346−27 are type 2 flares 7 .…”
Section: Sed Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…At fixed time binning, when long time intervals are used, a possible fast flux variation will be smoothed out, while using short bins might result in many upper limits during the low-activity periods. In the adaptive binning approach, the time bin widths are adjusted to produce bins with constant flux uncertainty above the optimal energy (E 0 ) and this appraoch is proved to be a powerful method to search for γ-ray flux variation (e.g., Rani et al 2013b;Sahakyan et al 2018;Baghmanyan et al 2017;Gasparyan et al 2018;Dutka et al 2017;Zargaryan et al 2017). E 0 depends on the flux and photon index of each source and can be computed following Lott et al (2012).…”
Section: γ-Ray Variabilitymentioning
confidence: 99%
“…The multiwavelength "snapshots" of blazar activity, i.e., the SEDs, can provide important clues to the emission processes and the physical parameters related to them within the relativistic jet, at least within a particular model set. This is usually attempted through solving the kinetic equation of the population of electrons injected with a certain energy distribution and evolving under radiative and adiabatic energy losses in, and escaping from, a single emission zone (Chiaberge & Ghisellini 1999;Lindfors et al 2005;Sikora et al 2009;Abdo et al 2011a,b;Paliya et al 2015;Hayashida et al 2015;Aleksić et al 2015;Saito et al 2015;Dutka et al 2017;Hu et al 2021). Such modeling efforts usually include an additional accretion disk component to fully describe the SED, although this component is more often necessary in the case of FSRQs (e.g., Castignani et al 2013; Sbar- Panel (a) gives the 7-day integration bin γ-ray fluxes from the Fermi-LAT satellite (0.1-300 GeV).…”
Section: Introductionmentioning
confidence: 99%